Evolution of Thoracic Surgery at BP Koirala Memorial Cancer Hospital, Nepal: An 18 – Year Journey of Innovation and Growth. - Thakur, Binay; Devkota, Mukti; Khatiwada, Sagar; Tiwari, Manoj; Bhattarai, Shachee; Kharel, Asish; Adhikari, Mahesh Mani; Sapkota, Sandeep (Nepalese Journal of Cancer, 2025)
Background: Thoracic malignancies constitute 15% of Nepal’s cancer burden, with lung cancer being the leading malignancy. This study aims at evolution of thoracic oncosurgery services at BP Koirala Memorial Cancer Hospital (BPKMCH) - Nepal’s premier tertiary cancer hospital during a period of 18 years (2007- 2025) to highlight procedural innovations, survival trends and resource-adapted strategies. Methods: a retrospective analysis of 8683 surgical procedures stratified into: Foundation (2007-2010; open surgery), Expansion (2011-2015; Minimally Invasive transition), and Modernization (2016-2025, June; precision surgery). Data sources included hospital records, surgical database, and institutional publications. Results: major surgeries increased 9-fold (106 in 2007 to 951 in 2024). Video-assisted thoracic surgery (VATS) biopsies achieved 98% diagnostic yield. Minimally invasive esophagectomy (MIS esophagectomy) rose from 0% to 80% (p <0.001) with 5-OS improvement from 17% to 27% (p=0.003). Pioneering milestones included Nepal’s first minimally invasive esophagectomy (2009), VATS Thymectomy (2011), Subxiphoid Uniportal Non-intubated Thymectomy (2025) and VATS non-intubated S9 sub lobar pulmonary resection (2025). Conclusion: BPKMCH has become Nepal’s thoracic surgery referral hub through phased innovation. Future priorities include expansion of non-intubated thoracic surgeries and robotic surgeries.